Two end-member earthquake preparations illuminated by foreshock activity on a meter-scale laboratory fault - Yamashita, Futoshi; Fukuyama, Eiichi; Xu, Shiqing; Kawakata, Hironori; Mizoguchi, Kazuo; Takizawa, Shigeru (Nature communications, 2021)
The preparation process of natural earthquakes is still difficult to quantify and remains a subject of debate even with modern observational techniques. Here, we show that foreshock activity can shed light on understanding the earthquake preparation process based on results of meter-scale rock friction experiments. Experiments were conducted under two different fault surface conditions before each run: less heterogeneous fault without pre-existing gouge and more heterogeneous fault with pre-existing gouge. The results show that fewer foreshocks occurred along the less heterogeneous fault and were driven by preslip; in contrast, more foreshocks with a lower b value occurred along the more heterogeneous fault and showed features of cascade-up. We suggest that the fault surface condition and the stress redistribution caused by the ongoing fault slip mode control the earthquake preparation process, including the behavior of foreshock activity. Our findings imply that foreshock activity can be a key indicator for probing the fault conditions at present and in the future, and therefore useful for assessing earthquake hazard. By tuning fault surface heterogeneity, the authors report earthquake preparation processes respectively driven by preslip and cascade-up on a meter-scale laboratory fault. The findings suggest that foreshock activity can be useful for predicting when and how the impending mainshock will occur.